Пошаговое объяснение:
441738 : (493 + x) = 69
493 + х = 441738 : 69
493 + х = 6402
х = 6402 - 493
х = 5909
441738:(493+x)=69 x=-493
441738/493+x=69
441738=69(493+x)
6402=493+x
-x=493-6402
-x=-5909
x=5909 x= -493
x=5909
Если не правильно сорян)))
Пошаговое объяснение:
441738 : (493 + x) = 69
493 + х = 441738 : 69
493 + х = 6402
х = 6402 - 493
х = 5909
441738:(493+x)=69 x=-493
441738/493+x=69
441738=69(493+x)
6402=493+x
-x=493-6402
-x=-5909
x=5909 x= -493
x=5909
Пошаговое объяснение:
Если не правильно сорян)))